2016
DOI: 10.1088/1757-899x/149/1/012161
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effect of pre-crack length variation on Inter-laminar fracture toughness of a Glass Epoxy laminated composite

Abstract: Abstract. Laminates of fiber reinforced polymer composites are good in in-plane properties and inherently weak in through thickness direction. To address this through thickness properties, the inter-laminar fracture toughness (G Ic and G IIc ) of a unidirectional (UD) Glass epoxy composite laminates were subjected to Mode-I and Mode-II loadings. Experiments were conducted using Double cantilever beam (DCB) and End notch flexure (ENF) specimens with varying pre-crack lengths. Mode I energy release rate (G Ic ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Damage deformation mechanisms are instrumental in redistributing the overstresses around the notch; therefore, improving their fracture behavior [5][6][7]. In addition, various specimen types such as compact *Corresponding Author Institutional Email: eng_mahmoudsamir@yahoo.com (M. S. EL-Wazery) tension specimens (CTS), end notch flexure (ENF) specimens and single edge notch bending (SENB) were used to evaluate the mode-I fracture toughness [8][9][10]. Jung and Kim [11] investigated the fracture toughness of carbon-glass/epoxy hybrid composites after fabricate by using vacuum assisted resin transfer molding and found that the fracture toughness reduced with increasing in glass fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…Damage deformation mechanisms are instrumental in redistributing the overstresses around the notch; therefore, improving their fracture behavior [5][6][7]. In addition, various specimen types such as compact *Corresponding Author Institutional Email: eng_mahmoudsamir@yahoo.com (M. S. EL-Wazery) tension specimens (CTS), end notch flexure (ENF) specimens and single edge notch bending (SENB) were used to evaluate the mode-I fracture toughness [8][9][10]. Jung and Kim [11] investigated the fracture toughness of carbon-glass/epoxy hybrid composites after fabricate by using vacuum assisted resin transfer molding and found that the fracture toughness reduced with increasing in glass fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few studies in the literature dealing with the effect of precrack length variation on fracture toughness of fibers‐reinforced laminated composites . By means of experiments conducted on Double cantilever beam and End notch flexure specimens with varying precrack lengths, the mode I and mode II energy release rates ( G Ic and G IIc ) can be evaluated in polymer‐based composites laminates . The experimental results reveal that, G Ic fracture toughness increases with increasing precrack length, whereas the effect of increase in precrack length exhibits reduced fracture toughness G IIc of UD glass‐fibers reinforced composites .…”
Section: Introductionmentioning
confidence: 99%
“…By means of experiments conducted on Double cantilever beam and End notch flexure specimens with varying precrack lengths, the mode I and mode II energy release rates ( G Ic and G IIc ) can be evaluated in polymer‐based composites laminates . The experimental results reveal that, G Ic fracture toughness increases with increasing precrack length, whereas the effect of increase in precrack length exhibits reduced fracture toughness G IIc of UD glass‐fibers reinforced composites . The influence of crack length and delamination width on the mode‐III energy release rate of laminated composites has also been investigated in the case of UD glass fibers reinforced polyester laminates .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding interlaminar fracture behavior, a number of studies in which various specimens were tested have been reported recently. Huddar et al [8] reported the effect of initial crack length on mode I interlaminar fracture toughness of glass fiber/epoxy laminated composites. They observed that the interlaminar fracture toughness at crack initiation increased with increasing initial crack length.…”
mentioning
confidence: 99%